Analisis Implementasi Standar Pelaporan Keuangan Internasional (IFRS) Terhadap Kinerja Keuangan Perusahaan - Nurlaila Nurlaila; Azka Wardatul Hayyah; Nur Habibah; Ayu Raudah Zamzam; Very Armanda Siregar (Trending: Jurnal Manajemen dan Ekonomi, 2025)
This study aims to analyze the impact of the implementation of International Financial Reporting Standards (IFRS) on the company's financial performance. The implementation of IFRS is expected to improve the transparency and quality of financial reporting, which in turn can affect the economic and financial decisions made by management and stakeholders. This study uses a quantitative method by analyzing the company's financial data before and after the implementation of IFRS. The data used include annual financial reports from various industrial sectors over a certain period of time. The results of the study indicate that the implementation of IFRS has a significant effect on several financial performance indicators, such as profitability, liquidity, and leverage. These findings suggest that higher and more consistent reporting standards can help companies manage their finances more effectively and increase investor confidence. However, the impact of IFRS implementation also varies depending on the characteristics of the industry and the accounting policies adopted by each company. This study makes an important contribution to the understanding of how international reporting standards can affect the company's financial performance and provides insights for regulators, practitioners, and academics in developing financial reporting policies.